The 'New' Paternalism, Consultation and Consent: Expectations of UK Participants in Defined Contribution and Self-Directed Retirement Savings Schemes. - Clark, G; Knox-Hayes, J (Palgrave Macmillan, 2009)
Concern about the competence of individual decision-makers has prompted governments and pension plan sponsors to take advantage of the insights gleaned from the behavioural revolution. Auto-enrolment, target-date, and related investment strategies may effectively counter behavioural biases such as inertia and the lack of attention paid to financial planning. Nonetheless, some participants may expect consultation when plan sponsors and management implement 'default' strategies and the like. Here, we assess the expectations of plan participants drawn from a national representative sample of UK residents who participate in defined contribution and personal pension schemes. It is found that respondents who expressed an interest in a high degree of consultation for the pathway to retirement were older, have higher incomes and recognised the significance of retirement saving schemes for their long-term welfare. A significant number of respondents would not or could not offer an opinion on the desirability of consultation. These respondents can be characterised as discouraged or disenchanted or disaffected, and socio-economic variables were not good predictors of these respondents' opinions of and attitudes towards consultation. Our results support, in part, the 'new' paternalism but raise questions about the blanket application of related measures to heterogeneous groups of plan participants.